Proyeksi Kebutuhan Air Minum Penduduk Kelurahan Balai Panjang dan Kelurahan Limbukan Kecamatan Payakumbuh Selatan Kota Payakumbuh Sampai Tahun 2021 - Nurul Falah; Jecky Asmura; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Drinking water is a qualified health water and it can be drink directly. Water drinked demand consist of domestic and non domestic or also known as the amounth of water reasonably necessary for basic human need and for other activity which need water. Water drinking demand in Balai Panjang village and Limbukan village are count base on population projection use four methods and the elected is geometric method. From the counting result, prediction of population in both the village until 2021 reach 4.536 people, which is in this plan, all of citizen will underserved with water drinking by house connecting type. Total of water demand average in both of village are 3,780 ltr/sec with rate of water loss are 20%. So, total water drinking demand in Balai Panjang village and Limbukan village until 2021 reach 4,536 ltr/sec.Keywords: Air Minum, Kebutuhan Air Minum, Pertumbuhan Penduduk, Proyeksi Geometri.